2000
DOI: 10.1034/j.1399-3003.2000.15e08.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of azithromycin on ozone-induced airway neutrophilia and cytokine release

Abstract: Exposure of humans to ozone causes increased neutrophils and inflammatory cytokines in airway lining fluid. Recent research shows that macrolide antibiotics may reduce interleukin (IL)-8 production by bronchial epithelial cells and inhibit neutrophil chemotaxis.A double-blind, cross-over study was performed in which 12 healthy subjects underwent two separate 4-h exposures to 0.2 parts per million ozone while exercising intermittently. In the 73.5 h before exposure, subjects were pretreated with either 1,250 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Such realistic exposures are more representative and informative than studies conducted under controlled exposure conditions, such as those in Table 1. All of the uncontrolled exposure studies concluded that a potential benefit for antioxidant supplementation in attenuating the negative effects of air pollution is evident; these findings are consistent with previous studies investigating the role of various anti-inflammatory interventions, for example azithromycin [37], indomethacin [38], cyclooxygenase metabolites [39] and budesonide [40] on pollution induced lung outcome. However, such consistency does not refute the need for more research on the subject.…”
Section: Discussionsupporting
confidence: 83%
“…Such realistic exposures are more representative and informative than studies conducted under controlled exposure conditions, such as those in Table 1. All of the uncontrolled exposure studies concluded that a potential benefit for antioxidant supplementation in attenuating the negative effects of air pollution is evident; these findings are consistent with previous studies investigating the role of various anti-inflammatory interventions, for example azithromycin [37], indomethacin [38], cyclooxygenase metabolites [39] and budesonide [40] on pollution induced lung outcome. However, such consistency does not refute the need for more research on the subject.…”
Section: Discussionsupporting
confidence: 83%
“…Several animal studies demonstrated that AZM attenuated many types of experimental airway inflammation caused by the allergic inflammation [15], by the inhalation of irritant gas, ozone [16], by the lung ischemia reperfusion injury [17], or by bacterial and viral infections [18, 19] in lower airways. In the present study, AZM also attenuated antigen- or LPS-induced mucus production in rat nasal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, neutralizing antibodies to IP-10, KC/IL-8, and monocyte chemoattractant protein (MCP)-3 also deplete ozone-mediated airway neutrophilia in murine studies [37]. Contrary to the effects of macrolides in minimizing airway neutrophilia in multiple species, azithromycin administration has little effect on altering ozone-induced BAL fluid neutrophils [38]. In a recent study, the unprecedented ability of a novel 24–amino acid peptide (MANS, homologous to N-terminal of MARCKS protein) to substantially inhibit fMLF-( N -formyl-methionyl-leucyl-phenylalanine)–mediated neutrophil migration in vitro has been reported [39].…”
Section: Discussionmentioning
confidence: 99%